(untitled) (KYAMC Journal, 2019)
Rasmussen’s aneurysm is an inflammatory pseudo-aneurysmal dilatation of a branch of pulmonary artery associated with a cavitary lung lesion. Like any aneurysm, a Rasmussen’s aneurysm is at increased risk of rupture and bleeding into the lungs. A 52 years old male presented with low-grade fever and haemoptysis, chest x-ray revealed a well margined nodular shadow with calcifications in mid zone of left lung associated with ipsilateral upper zone fibrosis and bronchiectasis. The patient had past history of pulmonary tuberculosis eight years back. For characterization of left pulmonary nodule the patient was referred to radiology and Imaging department and contrast CT scan of chest was done. Contrast CT scan of chest with reformat MIP pulmonary angiogram revealed a small pulmonary artery vascular malformation in lateral basal segment of lower lobe of left lung associated with left upper lobar cavitating lesion with fibrosis, traction bronchiectasis and Rasmussen’s aneurysm arising from upper lobar apical segmental pulmonary artery. Early surgical or angiographic interventions with endovascular embolization are recommended once it be clearly diagnosed. KYAMC Journal Vol. 10, No.-3, October 2019, Page 168-170